Studi Literatur: Pendekatan Human Element pada Buku Teks Chemistry Human Activity, Chemical Reactivity Karya Mahaffy dkk Materi Kesetimbangan Asam Basa dalam Larutan - Widia Hizriati; Faizah Qurrata Aini (Entalpi Pendidikan Kimia, 2022)
A variety of skills have shaped the teaching and learning of chemistry in the early 21st century. This includes fundamental changes in chemistry such as changes in understanding of how students learn, the application of computer and information technology in studying complex scientific phenomena, and others. Responding to this problem, chemistry education which originally used a "triangle shape" must be emphasized into a "tetrahedral" form, where the fourth peak represents the human context in studying chemistry or is called the human element. Highlighting the human element provides compelling reasons to emphasize case studies, active learning, and investigative projects to link school chemistry to everyday life. This study aims to describe the phenomena that exist regarding the human element in chemistry learning, especially in textbooks. This research is a qualitative research with descriptive analysis technique with library research. The data used are secondary data derived from textbooks and scientific articles. The existence of human activities involved in learning chemistry provided in textbooks, helps students learn from rich contexts. Learning from a rich context makes learning chemistry more motivating, interesting and relevant to their lives, thus helping students understand chemical concepts well. Therefore, the importance of the human element involved in learning chemistry, especially in textbooks.